2019
DOI: 10.1002/spp2.1252
|View full text |Cite
|
Sign up to set email alerts
|

Early Triassic benthic invertebrates from the Great Bank of Guizhou, South China: systematic palaeontology and palaeobiology

Abstract: To further our understanding of the evolution, selectivity and ecological composition of marine communities following the latest Permian mass extinction, new collections from underrepresented regions in the immediate extinction aftermath are required. Here, we provide new systematic data and the first palaeobiological account of the benthic invertebrate community from the Great Bank of Guizhou, South China. We systematically describe three brachiopod species, 26 bivalve species, 11 gastropod species, 1 microco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 129 publications
(204 reference statements)
0
17
0
Order By: Relevance
“…Studies of living microbialites have observed metazoans exploiting local oxygen refugia within the microbialites (e.g., Gingras, Lalond, Amskold, & Konhauser, ; Rishworth, Perissinotto, & Bird, ; Tarhan, Planavsky, Laumer, Stolz, & Reid, ). These metazoans, however, are typically soft‐bodied, infaunal, and motile, which is not consistent with the epifaunal, stationary lifestyles of the benthic communities reported from the Great Bank of Guizhou (Foster et al., ). In addition, if the microbial mats were a preferable environment, we would expect that the microbial facies would contain a greater species richness and abundance than the surrounding non‐microbial rocks, which was not observed in this study (Figures and ).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Studies of living microbialites have observed metazoans exploiting local oxygen refugia within the microbialites (e.g., Gingras, Lalond, Amskold, & Konhauser, ; Rishworth, Perissinotto, & Bird, ; Tarhan, Planavsky, Laumer, Stolz, & Reid, ). These metazoans, however, are typically soft‐bodied, infaunal, and motile, which is not consistent with the epifaunal, stationary lifestyles of the benthic communities reported from the Great Bank of Guizhou (Foster et al., ). In addition, if the microbial mats were a preferable environment, we would expect that the microbial facies would contain a greater species richness and abundance than the surrounding non‐microbial rocks, which was not observed in this study (Figures and ).…”
Section: Discussionmentioning
confidence: 55%
“…Therefore, this explains why the microbialites record a benthic community and why the non‐microbial fabric contains significantly more bioclasts than the microbial fabric. Systematic studies of the species that occur in the microbialites also find that at both the genus and species levels the microbialites did not contain a unique suite of benthic invertebrates, and these taxa are also mainly characterized as cosmopolitan taxa (Foster et al., ; Hautmann et al., ). This observed difference between microbial and non‐microbial facies contradicts the definition of a refugium (i.e., an area which a population can survive through periods of unfavorable conditions), implying that microbialites were not a refuge in the aftermath of the latest Permian mass extinction.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of such obligate aerobes was not used to falsify anoxic conditions, but instead, the microbial mat communities that precipitated the buildups were interpreted as unique oxygenated refugia in otherwise anoxic settings; this is known as the microbialite refuge hypothesis (Forel et al , ). Even though microbial mats can provide oxygenated refugia in hypoxic and anoxic environments (Gingras et al , ), the fauna that occurs in the Early Triassic microbialites are mostly not animals that can live within a microbial mat (Foster et al , ). In addition, the fossils within the microbialites are allochthonous and have been transported around and into the microbial frameworks, thus the animals did not apparently live within the microbial mats (Foster et al , ) (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…The microbial buildups on the Great Bank of Guizhou occur within a narrow range of environmental conditions. The thickest microbialite successions occur on the inner platform and are intercalated with oolitic and skeletal packstones and grainstones that contain a diverse, para‐autochthonous assemblage (Foster et al , ). Cross‐bedding can be recognized in the grainstones that drape over the microbialites.…”
Section: Geological and Palaeoenvironmental Settingmentioning
confidence: 99%
“…This is exemplified by the fact that there are currently only three species known from relatively well-preserved echinoid tests from Lower Triassic strata (Linck, 1955; Kier, 1968b; Godbold et al, 2017). Despite the rarity of well-preserved specimens, disarticulated echinoid plates and spines are abundant throughout Lower Triassic strata (Broglio Loriga, Masetti & Neri, 1983; Schubert & Bottjer, 1995; Moffat & Bottjer, 1999; Rodland & Bottjer, 2001; Fraiser & Bottjer, 2004; Nützel & Schulbert, 2005; Mata & Woods, 2008; McGowan, Smith & Taylor, 2009; Hofmann et al, 2013; Pietsch et al, 2019; Foster et al, 2018; Foster et al, 2019a; Foster et al., 2019b), though they are typically identified in thin section (e.g., Noé, 1987; Krystyn et al, 2003; Posenato, 2009; Foster et al, 2019a; Foster et al., 2019b). A potential source of “hidden diversity” comes from this disarticulated material (Twitchett & Oji, 2005; Pietsch et al, 2019) as echinoid coronal plates, like the ossicles of other echinoderm groups, display morphological features characteristic of both higher, and lower, taxonomic levels (Gordon & Donovan, 1992; Nebelsick, 1992; Nebelsick, 1995; Nebelsick, 1996; Donovan, 2001; Thompson & Denayer, 2017).…”
Section: Discussionmentioning
confidence: 99%